Transition from child to adult mental health services: a French retrospective survey. Issue 5 (7th November 2016) - Schandrin, Aurélie; Capdevielle, Delphine; Boulenger, Jean-Philippe; Batlaj-Lovichi, Monique; Russet, Frédérick; Purper-Ouakil, Diane
Abstract : Purpose: Adolescents and young adults' mental health problems are an important health issue. However, the current organisation of the care pathway is not robust enough and transition between child and adolescent mental health services (CAMHS) and adult mental health services (AMHS) has been identified as a period of risk. The paper aims to discuss these issues. Design/methodology/approach: A retrospective survey was conducted in Montpellier University Hospital concerning transitions organised between CAMHS and AMHS between 2008 and 2009. The aim was to assess if transitions met four criteria identified in literature as warranting an optimal transition. Findings: In total, 31 transitions were included. Transition was accepted by AMHS in 90 per cent of cases but its organisation was rarely optimal. Relational continuity and transition planning were absent in 80 per cent of cases. The age boundary of 16 often justified the triggering of the transition regardless of patient's needs. Discontinuity was observed in 48 per cent of transition cases, with an average gap of three months without care. Psychiatrists reported difficulties in working together. Finally, at the moment of the survey (one to three years later), 55 per cent of patients were lost to follow-up. Research limitations/implications: This is a retrospective study on a small sample but it reveals important data about transition in France. Practical implications: Transition process should include collaborative working between CAMHS and AMHS, with cross-agency working and periods of parallel care. Social implications: Transition-related discontinuity of care is a major socioeconomic and societal challenge for the EU. Originality/value: Data related to the collaboration between CAMHS and AMHS services are scarce, especially regarding the transition in France.